تأثير التسميد المعدني والعضوي في نمو نبات الزينيا وإزهارها (Zinnia elegans) - نصّور مازن; هيفا سوسن; قاسم رنا (Latakia University Journal -Biological Sciences Series, 2013)
هدف هذا البحث إلى تحديد دور كل من التسميد المعدني (N.P.K) والعضوي (زرق الدجاج, زبل الأبقار, زرق الدجاج مع زبل الأبقار) في النمو الخضري والإزهار لنبات الزينيا (Zinnia elegans), إضافةً لإمكانية الاعتماد على هذه الأسمدة العضوية في تأمين المواد الغذائية اللازمة للنبات بهدف الحد من التسميد المعدني. أظهرت النتائج أن استخدام التسميد المعدني 30,20,20 :NPK) غ/م2) أو التسميد بزرق الدجاج (2 كغ/م2) أسهم بشكل إيجابي في النمو الخضري (طول النبات, متوسط عدد التفرعات ومتوسط عدد الأوراق على النبات) إضافةً للأثر الإيجابي في تشكل الأزهار وتطورها (التبكير في الإزهار, عدد الأزهار على النبات وحجم الأزهار) وفي نسبة المادة الجافة سواء في المجموع الخضري أم الزهري. كما أشارت النتائج إلى أن النباتات المسمدة بالـ NPK أو بزرق الدواجن قد حققت إنتاجاً أكبر من الأزهار وعائداً اقتصادياً أعلى قياساً بمعاملة الشاهد وبمعاملة السماد العضوي البقري. The aim of this research is to determine the role of mineral (NPK) and organic fertilization (Chicken manure, Cow manure and Chicken with Cow manure) on vegetative growth and flowering of Zinnia (Zinnia elegans). This research also examines the possibility of relying on this organic manure to present nutrients for the plant in order to reduce mineral fertilization. The results show that the use of NPK (30, 20, 20 g/m2) or Chicken manure (2Kg/m2) has a positive impact on vegetative growth (plant height and average number of branches andleaves on the plant). They also show a positive effect on the flower developmentand flowering (early flowering, number of flowers and flower volume). These positive effects are reflected on the proportion of dry matter both in the vegetative and flowering part. The results indicate that plants fertilized with NPK or Chicken manure realize higher economic profit than the control and those fertilized with Cow manure.